Biatrial Approach Provides Better Outcomes in the Surgical Treatment of Cardiac Myxomas - Yüksel,Ahmet (2016)
Abstract Objective: We aimed to present clinical features, surgical approaches, importance of surgical technique and long-term outcomes of our patients with cardiac myxoma who underwent surgery. Methods: We retrospectively collected data of patients with cardiac myxoma who underwent surgical resection between February 1990 and November 2014. Biatrial approach is the preferred surgical method in a large proportion of patients that are operated due to left atrial myxoma because it provides wider exposure than the uniatrial approach. To prevent recurrence during surgical resection, a large excision is made so as to include at least 5 mm of normal area from clean tissue around the tumor. Moreover, special attention is paid to the excision that is made as a whole, without digesting the fragment of tumor with gentle dissections. Results: Forty-three patients (20 males, mean age of 51.7±8.8 years) were included. Most common symptom was dyspnea (48.8%). Tumor was located in the left atrium in 37 (86%) patients. Resections were achieved via biatrial approach in 34 patients, uniatrial approach in 8 patients, and right atriotomy with right ventriculotomy in 1 patient. One patient died due to low cardiac output syndrome in the early postoperative period. Mean follow-up time was 102.3±66.5 months. Actuarial survival rates were 95%, 92% and 78% at five, 10 and 15 years, respectively. Recurrence was observed in none of the patients during follow-up. Conclusion: Although myxomas are benign tumors, due to embolic complications and obstructive signs, they should be treated surgically as soon as possible after diagnosis. To prevent recurrence, especially in cardiac myxomas which are located in left atrium, preferred biatrial approach is suggested for wide resection of the tumor and to avoid residual tumor.